Perburuan dan Perdagangan Biawak Air, Varanus salvator (Laurenti, 1768) di Daerah Bogor - Andhika Prima Yudha; Mirza Dikari Kusrini; Evy Arida (Journal of Tropical Ethnobiology, 2021)
The Water Monitor, Varanus salvator, is mostly caught for its skin and meat in Indonesia. The purpose of the research was to investigate hunting and trade of water monitor in Bogor area, West Java. Data was collected between March and June 2020 which include data of hunters’ characteristics, hunting methods, habitat of hunted water monitors and trade in Bogor. We conducted interviews to 42 hunters and following four groups of hunters during their hunting session. Generally, hunters were students, workers, or laborers, which only hunt during weekend. To capture water monitor, hunter used dogs and air rifles, although some used bare hands. Capture habitats are in river basins, around settlements, shrubs, rice fields and river banks. There is no specialized water monitor collectors for trade as they are not highly sought in the last two years. However, occasionally there is a demand for household consumption, food stalls, and to be used as medicinal ingredients. In addition, there are online sales systems specifically for pets.